2004
DOI: 10.1037/0022-3514.86.6.814
|View full text |Cite
|
Sign up to set email alerts
|

The Redux of Cognitive Consistency Theories: Evidence Judgments by Constraint Satisfaction.

Abstract: The authors suggest that decisions made from multiple pieces of evidence are performed hy mechanisms of parallel constraint satisfaction, which are related to cognitive consistency theories. Such reasoning processes are bidirectional--decisions follow from evidence, and evaluations of the evidence shift toward coherence with the emerging decision. Using a factually complex legal case, the authors observed patterns of coherence shifts that persisted even when the distribution of decisions was manipulated (Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
244
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(283 citation statements)
references
References 102 publications
34
244
1
4
Order By: Relevance
“…Thagard and colleagues have demonstrated convincingly that a strategic selection of plans (Thagard & Millgram, 1995), as well as jury decisions (Thagard, 2003), could be plausibly simulated by employing a parallel constraint satisfaction (PCS) network. Furthermore, Holyoak, Simon and colleagues (Holyoak & Simon, 1999;Simon, Krawczyk, & Holyoak, 2004;Simon, Snow & Read, 2004) showed that individuals tend to increase coherence even while the decision is made. Note that such coherence shifts cannot be explained by either rational choice models or simple heuristics, which share the assumption that stimulus information remains stable during subsequent decision processes once it is represented in the mind (Brownstein, 2003;.…”
Section: A Connectionist Approach To Decision Makingmentioning
confidence: 99%
“…Thagard and colleagues have demonstrated convincingly that a strategic selection of plans (Thagard & Millgram, 1995), as well as jury decisions (Thagard, 2003), could be plausibly simulated by employing a parallel constraint satisfaction (PCS) network. Furthermore, Holyoak, Simon and colleagues (Holyoak & Simon, 1999;Simon, Krawczyk, & Holyoak, 2004;Simon, Snow & Read, 2004) showed that individuals tend to increase coherence even while the decision is made. Note that such coherence shifts cannot be explained by either rational choice models or simple heuristics, which share the assumption that stimulus information remains stable during subsequent decision processes once it is represented in the mind (Brownstein, 2003;.…”
Section: A Connectionist Approach To Decision Makingmentioning
confidence: 99%
“…Solution aversion may also be at least in part a product of people's general tendency to seek cognitive coherence (Osgood & Tannenbaum, 1955;Simon, 2004;Simon, Krawczyk, Bleicher, & Holyoak, 2008). As Simon, Snow, and Read (2004) explained, "Coherent representations are ones in which elements that are positively related to one another tend to wax and wane together" (p. 816). In the case of the current climate experiments, it would be highly incoherent to be averse to and nonsupportive of environmental solutions but also believe in the environmental problem, insofar as the belief in the problem may more or less imply the enactment of the specific solutions.…”
Section: Relation To Other Theoretical Modelsmentioning
confidence: 99%
“…Thus, actions may reform beliefs and attitudes which may recursively alter further actions. This is a process of coherence-driven processing (Simon, Snow, & Read, 2004), that enables confidence in decision-making by bringing the various pieces of the cognitive field into consonance (Simon & Holyoak, 2002).…”
Section: Cognitive Theory and Learning In Networkmentioning
confidence: 99%